Pengaruh Pemberian Terapi Murottal Al-Quran Surah Al-Isra terhadap Hemodinamik pada Pasien Stroke - Habab Handal Al Harod; Wahyu Rima Agustin; Wahyuningsih Safitri (Universitas Muhammadiyah Klaten, 2024)
Abstract Stroke is a disease caused by a blockage or haemorrhage in the blood vessels of the brain that can block or reduce the blood supply to the brain. The provision of Al-Quran therapy is a non-pharmacological therapy that can be used in managing pain. The research can be classified as quantitative, with a quasi-experimental approach. This research data sampling technique is non probability sampling. The sample used was 30 stroke patients. The research tools used are observation sheets, headphones, mobile phones and murottal surah Al-Isra. The characteristics of respondents aged less than 50 years were observed in 14 respondents (46.7%) out of a total of 30 respondents, while respondents aged 50 years or older were observed in 16 respondents (53.3%) out of a total of 30 respondents. The characteristics of respondents according to gender revealed that 21 males (70.0%) out of a total of 30 respondents, while females constituted 9 respondents (30.0%) out of a total of 30 respondents. The results demonstrated a p-value of 0.000 for the variables of systolic and diastolic blood pressure, respiratory rate (RR), pulse, temperature, and oxygen saturation, with a p-value less than 0.05, indicating a statistically significant result. It can be concluded that Al-Quran Murottal Therapy has an effect on the haemodynamic status in stroke patients at Moewardi Hospital.